Tuberculosis and HIV—An Update on the “Cursed Duet” in Children - Fry, Samantha H.-L.; Barnabas, Shaun L.; Cotton, Mark F. (Frontiers in Pediatrics, 2019)
HIV and tuberculosis (TB) often occur together with each exacerbating the other. Improvements in vertical transmission prevention have reduced the number of HIV-infected children being born and early antiretroviral therapy protects against tuberculosis, these infants are still vulnerable to TB. With delayed HIV diagnosis, HIV infected infants often present with tuberculosis co-infection. The number of HIV exposed uninfected children has not declined. These infants have high exposure to TB and may be more immunologically vulnerable due to HIV exposure in utero. Bacillus Calmette-Guérin (BCG) immunization shortly after birth is essential for preventing severe TB in infancy. With early infant HIV diagnosis and antiretroviral therapy, disseminated BCG is no longer an issue. TB prevention therapy should be implemented whenever a source case is identified and for all HIV-infected individuals over a year of age. Although infection can be identified through skin tests or interferon gamma release assays, the non-availability of these tests should not preclude prevention therapy, once active TB has been excluded. Therapeutic options have moved from isoniazid only for 6 to 9 months to shorter regimens. Prevention therapy after exposure to a source case with resistant TB should also be implemented, but should not prevent pivotal prevention trials already under way. A microbiological diagnosis for TB remains the gold standard because of increasing drug resistance. Antiretroviral therapy for rifampicin co-treatment requires adaptation for those on lopinavir-ritonavir, which requires super-boosting with additional ritonavir. For those with drug resistant TB, the main problem is overlapping toxicity.